미디어음주장면 노출이 성인 음주문제수준에 미치는 영향: 긍정적 음주기대, 음주동기의 매개효과 - 박가영(KaYoung Park); 조희정(Heejeong Jo); 나세연(Sayeon Na); 이희종(Heejong Lee) (보건교육건강증진학회지, 2021)
Objectives: This study aimed to explore the effects of exposure to drinking scenes in media on drinking problems in adults and to understand the role of positive alcohol expectancy and drinking motivation. Methods: 1,057 adult men and women aged between 20 and 65 were recruited for an online survey and the size of the final sample analyzed was 961. Data were analyzed by descriptive statistics and hypothesis testing using SPSS 27.0 and SPSS Process Macro 3.5. The dual mediation effect was verified using Model 6. Results: Exposure to drinking scenes in media was found to have a direct influence on positive alcohol expectancy and drinking motivation. The more exposure to drinking scenes, the higher positive alcohol expectancy and drinking motivation, it made the drinking problems become worse It was also found that positive alcohol expectancy and drinking motivation fully mediated the effects of media exposures on drinking problems. Conclusion: We suggested that guidelines and regulations on exposure to drinking scenes in media need to be strengthened to prevent alcohol-related harms. Also, we proposed a follow-up study to understand the size of the effects of alcohol advertising and exposure to drinking scenes on drinking problems. KCI Citation Count: 1